Analisis Pengaruh Keputusan Pembelian Generasi Milenial pada Industri Kuliner di Kota Medan - saskia saskia; Ilham Mubaraq Ritonga; Aflin Roza; Muhammad Ridwan (Universitas Harapan Medan, 2019)
There are various kinds of businesses that can become business opportunities, one of which is a culinary business. Now adays more and more culinary producers are involved in fulfilling the needs and desires of consumers. This makes the culinary entrepreneur must strive to understand the needs, wants, and demands of the target market. The entrepreneur must try to get the attention and interest of consumers, because they compete with companies that have similar products. Therefore every entrepreneur with a similar type of product must think of ways to win the market. The population in this study is the millennial generation, male and female culinary enthusiasts in the city of Medan on the campus of Universitas Harapan Medan, students of the Faculty of Business Economics. The total population in this study was 876 students. This study will use random sampling of 100 respondents. Data analysis techniques using linear regression. The results of this study indicate that there is a significant influence of Word of Mouth on Consumer Culinary Purchasing Decisions in Medan City. There is a significant influence of Store Atmosphere on Culinary Consumer Purchasing Decisions in Medan. There is a significant influence of Store Image on Culinary Consumer Purchasing Decisions in Medan. There is a significant influence Word of Mouth, Store Atmosphere and Store Image on Purchasing Decisions of culinary consumers in Medan. The ability of Word of Mouth, Store Atmosphere and Store Image in explaining consumer purchasing decisions is 0.256 or equal to 25.6%. This means that Word of Mouth, Store Atmosphere and Store Image is able to explain Consumer Purchasing Decisions is 25.6%, the remaining 74.4% is explained by other variables not included in this research model